Nazwy osób (ze względu na cechy psychiczne) w polszczyźnie miejskiej Poznania - Piotrowicz, Anna; Witaszek-Samborska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The article presents the regional names of persons from Poznań, considering their psychic features attributed to denotations. The repertoire of features reflected in personal names of the urban dialect of Poznań (differentiated here only from the point of view of psychic features) confirms the conclusion drawn from the analysis of quotations illustrating individual entries of Słownik gwary miejskiej Poznania (“Dictionary of the Urban Dialect of Poznań”) edited by Monika Gruchmanowa and Bogdan Walczak (and published in an earlier article), that the stereotype and autostereotype of a resident of Poznań finds no reflection in those features. The characteristics regarded as typical for poznańska pyra* (*a negative designation of Poznań residents) constitute a meaningful core for just few names (e.g. avarice in regional lexemes gryzinera // gryzinyra or nyrol), whereas more numerous are the designations connoting ordinary vices (such as: excessive agility, dishonesty, cheekiness, roguery and hooliganism, infantilism and plaintiveness, mental heaviness, stupidity, clumsiness, untidiness, talkativeness, gossipiness, querulousness, gloominess and taciturnity, wickedness, vulgarity, arrogance etc.), characteristic for people in general, regardless of their place of residence.